Critical Thinking Skills in Assessment Essays to Improve Motivation and Learning Outcomes: Bibliometric Analysis - Hirahmah, Atifah; Yani, Intan Purnama; Festiyed, Festiyed; Emiliannur, Emiliannur (Jurnal Pijar Mipa, 2024)
As the demands of the modern world increase, critical thinking skills become increasingly important for students to succeed in education and life. Therefore, assessment essays are a tool to assess students' critical thinking skills. This research aims to analyse trends and developments in research on critical thinking skills in assessment essays to increase motivation and learning outcomes. This type of research is bibliometric analysis. Bibliometric methods are used to analyse scientific publications related to this topic. Data were collected from various scientific databases, including Scopus, Web of Science, and Google Scholar. The analysis results show that research on critical thinking skills in assessment essays has continued to increase in recent years. This topic is becoming increasingly important for educational researchers and practitioners. The analysis also indicates that this research comes from various scientific disciplines, such as physics. The main finding of this research is that critical thinking skills in assessment essays can increase student motivation and learning outcomes. This can be achieved by implementing various strategies, such as providing appropriate essay prompts, using clear grading rubrics, and providing constructive feedback to students. This research has several important implications for educational practice. First, this research shows that critical thinking ability is an essential skill for students to develop. Second, this research indicates that assessment essays can improve students' critical thinking skills. Third, this research guides teachers and other educators on effectively implementing essay assessments to increase student motivation and learning outcomes.